2016
DOI: 10.1186/s12936-016-1642-6
|View full text |Cite
|
Sign up to set email alerts
|

Field effectiveness of microbial larvicides on mosquito larvae in malaria areas of Botswana and Zimbabwe

Abstract: BackgroundThe successful control of malaria vectors requires the control of both the larval and adult stages. The adult control methods through indoor residual spraying (IRS) and use of long-lasting insecticidal nets (LLINs) continue to be widely used with some high measure of success. Larval control methods are also being used by a number of National Malaria Control Programmes (NMCPs) with limited understanding of its contribution. Larval control might be needed in some areas to move from malaria control to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…For publications involving multi-country studies, each country was counted towards the total, e.g. Kenya and Tanzania [94] and Botswana and Zimbabwe [79]. Note : Zaire: now The Democratic Republic of the Congo…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For publications involving multi-country studies, each country was counted towards the total, e.g. Kenya and Tanzania [94] and Botswana and Zimbabwe [79]. Note : Zaire: now The Democratic Republic of the Congo…”
Section: Resultsmentioning
confidence: 99%
“…funestus Not specified[85]Bobirwa, Botswana; Buhera, ZimbabweRuralJun 2015–Sep 2015; Aug 2012–Oct 2013 An. arabiensis Riverbed pools/drains, hoof prints[79, 81]Anseba, Gash-Barka, Debub and North Red Sea zones, EritreaRuralNot stated An. arabiensis Pools, canals, swamps, dams, stream bed pools, wells, ponds[88, 89]Chikhwawa, MalawiRuralMay 2016–April 2018Not statedNot stated[90]Nouna, Burkina FasoRural2013–2015 An.…”
Section: Resultsmentioning
confidence: 99%
“…israelensis (Bti) and Bacillus sphaericus (Bs) can target both insecticide resistant and outdoor biting malaria vectors [ 15 – 17 ]. Several studies in Africa have demonstrated the effectiveness of these bacterial larvicides in granular, powder and tablet formulations in reducing the density of malaria vectors [ 15 , 18 27 ] and malaria transmission [ 23 , 28 ]. However, these formulations are of short duration of activity and hence require regular applications which are associated with high operational costs as compared to the longer-lasting chemical-based interventions; hence, their use has not been widely embraced by the national malaria control programs in sub-Saharan Africa [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…IRS, which is implemented in six malaria-endemic districts in Botswana is the main vector control intervention and is supplemented by LLINs (first introduced in 2010 through mass distribution) and larviciding with Bacillus thuringiensis serovar israelensis [ 11 , 29 ] (Table 1 ). Since 2013, larviciding is occasionally implemented in 3 districts whose water bodies are amenable for the intervention [ 6 , 29 ] and has been shown to reduce larval densities which could reduce malaria risk due to low adult emergence [ 20 , 44 ].…”
Section: Botswana Malaria Situation Analysismentioning
confidence: 99%
“…LSM is a population suppression technique that can be further classified into (i) habitat modification, (ii) habitat manipulation, (iii) biological control, and (iv) larviciding [16]. Larviciding with microbial larvicides has been shown to reduce vector populations in various settings [17][18][19][20][21]. This is achieved by killing mosquito larvae and pupae and/or getting rid of breeding sites, thereby reducing adult density and possibly the number of infective bites per person per year [22].…”
Section: Introductionmentioning
confidence: 99%